Manajemen Supervisi Pendidikan di Era Digital - Septria Sa'duh; Muhammad Zidan Firmansyah; Makruf; Ahmad Sabri; Yusran Lubis (STIKes Ibnu Sina Ajibarang, 2024)
Effective management of educational supervision is key in improving the quality of education and facilitating teachers' professional development in the ever-changing modern era. This study aims to analyze how educational supervision management can be optimized through the use of technology in the digital era. The research method used in this study is a literature study, which aims to analyze and review literature related to educational supervision management in the digital era. The results of this study show that education supervision management has a crucial role in facing dynamic changes in the digital era. By encouraging the application of technology and developing teachers' digital competencies, supervision management can create a more innovative and effective learning environment. In addition, the use of data for decision-making, collaboration between teachers and the implementation of a performance-based assessment system will improve the quality of learning and the development of teacher professionalism. Adaptation to change and the application of effective change management approaches are key to ensuring that changes in education have a positive impact. Thus, educational supervision management needs to continue to innovate and adapt in order to meet the demands and challenges of education in the digital era, and make a significant contribution to the quality of education.